Sealed-off perforation of colorectal carcinoma initially interpreted as diverticulitis: intra-abdominal abscess as a diagnostic and therapeutic dilemma - Milina, Srđan; Nikolić, Marija; Trifunovic, Nemanja; Trifunović, Jovana; Abazović, Tanja (Medical Gazzette, 2026)
Introduction: Intraabdominal abscess often arises as a complication of gastrointestinal tract perforation caused by inflammatory diseases, trauma, or malignancy. Although most commonly associated with diverticulitis, perforation of colorectal cancer, especially in the form of a sealed-off perforation can present with an identical clinical manifestation, making timely diagnosis and treatment more difficult. While diverticulitis is frequently suspected, malignancy as the underlying cause of an abscess often remains undiagnosed during the acute phase.Case presentation: We present the case of a 61-year-old female admitted with fever, right lower quadrant abdominal pain, and laboratory signs of inflammation. Radiological findings revealed an abscess collection in the right iliac region, initially suggestive of complicated diverticulitis. The presence of dolichosigmoid colon with a right-sided (dextropositioned) sigmoid further complicated the diagnostic process. Initial treatment was conservative with antibiotic therapy, resulting in both clinical and radiological improvement. In the post-acute phase, protocol-mandated colonoscopy revealed a tumor in the sigmoid colon, along with extensive diverticulosis of the left colon. Histopathological examination confirmed adenocarcinoma. The patient subsequently underwent elective surgery with high anterior resection of the rectum and colo-rectal end-to-end anastomosis (without the need for stoma formation), followed by inclusion in an adjuvant oncological treatment protocol.Conclusion: Sealed-off perforation of colorectal carcinoma can clinically and radiologically mimic diverticulitis with abscess formation, potentially delaying the diagnosis of malignancy. In cases with atypical anatomy, thorough and complete diagnostic workup is essential, including mandatory colonoscopy after resolution of acute inflammation. This case highlights the importance of differential diagnosis in the initial phase and adherence to protocolized colonoscopic evaluation, which enables timely identification of colorectal cancer and improves treatment outcomes.
Keywords: intraabdominal abscess, sealed-off perforation, colorectal carcinoma, diverticulitis, dolichosigmoid